2012
DOI: 10.5653/cerm.2012.39.4.144
|View full text |Cite
|
Sign up to set email alerts
|

Maternal caffeine consumption has irreversible effects on reproductive parameters and fertility in male offspring rats

Abstract: ObjectiveConcerns are growing about the decrease in male reproductive health. Caffeine is one of the popular nutrients that has been implicated as a risk factor for infertility. In the present study, we examined whether in utero and lactational exposure to caffeine affects the reproductive function of the offspring of rats.MethodsPregnant rats received caffeine via drinking water during gestation (26 and 45 mg/kg) and lactation (25 and 35 mg/kg). Body and reproductive organ weight, seminiferous tubule diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 45 publications
5
44
1
Order By: Relevance
“…Consistent with previous reports (5,8), we observed significant reductions in both body weight gain and food intake in caffeine-fed immature animals (Fig. 1A, 1C), indicating that reduced body weight gain can be attributed mainly to decreased food intake.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous reports (5,8), we observed significant reductions in both body weight gain and food intake in caffeine-fed immature animals (Fig. 1A, 1C), indicating that reduced body weight gain can be attributed mainly to decreased food intake.…”
Section: Discussionsupporting
confidence: 93%
“…35,37 Prenatal caffeine exposure has been shown to lower testosterone levels in the male offspring of humans 39 and rats. 7 We found that pubertal caffeine exposure had similar effects on testosterone levels. However, several studies have reported that chronic caffeine consumption increased serum testosterone levels in adult humans 39 and animals.…”
Section: Discussionmentioning
confidence: 56%
“…Caffeine adversely affects endochondral ossification during the course of fetal skeletal growth, and maternal exposure to caffeine causes delayed and abnormal fetal skeletal development. [7][8][9] Although caffeine's detrimental effects on endochondral ossification during the prenatal period have been widely demonstrated, data on its effects on longitudinal bone growth during the pubertal growth spurt are particularly sparse. To the best of our knowledge, there are no interventional studies dedicated to assessing the effects of different doses and exposure durations of caffeine on skeletal development during puberty.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction is confirmed by the significant decrease in the sperm count of animals treated with caffeine (Table 3). This reduction in the weight of testes and epididymis might also be due to distortion in spermatogenesis as earlier stated and/or testicular degenerations as a result of the treatment (Wilcox et al, 1988;Dorostghoal et al, 2012).…”
Section: Discussionmentioning
confidence: 97%